Diallyl disulfide attenuates hydrogen peroxide-induced oxidative damage of ovine rumen epithelial cells through the nuclear factor erythroid-2 related factor 2 signaling pathway - Rui Pang; Qingyue Zhang; Yuxin Wang; Xiaona Dong; Li Huang; Yingying Tang; Chunhuan Ren; Yanfeng Xue; Zijun Zhang; Wen Zhu (Animal Nutriomics)
This study investigated the impact of diallyl disulfide (DADS) on oxidative stress induced by hydrogen peroxide (H2O2) in ovine rumen epithelial cells (RECs). Initially, the effects of DADS were evaluated on cellular reactive oxygen species (ROS) levels, antioxidant capacity in RECs were estimated. Then, RNA-seq analysis was conducted in DADS-treated and untreated cells to analyze the differential gene expression, as well as Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways. Finally, the effects of DADS on Kelch-like ECH associated protein 1/the nuclear factor erythroid 2-related factor 2 (Keap1/Nrf2) signaling pathway in RECs were evaluated. Results showed that DADS remarkably enhanced superoxide dismutase (SOD) activity and total antioxidant capacity (T-AOC) (P < 0.05) while reducing ROS and malonaldehyde production (P < 0.05) in H2O2-treated RECs. Transcriptomic analysis revealed that DADS might influence glutathione synthesis through cysteine and methionine metabolism, thereby affecting the transcription of genes involved in immunity and oxidative stress. The DADS treatment resulted in increased nuclear translocation of Nrf2 and upregulation of mRNA and protein levels of quinone oxidoreductase 1, heme oxygenase 1, and Nrf2. The Nrf2-specific inhibitor nullified the protective effects of DADS on malonaldehyde formation induced by H2O2 and decreased T-AOC and SOD activities. In conclusion, DADS demonstrated the ability to alleviate oxidative stress in RECs by promoting antioxidative capacity through the Keap1/Nrf2 signaling pathway.